Unfinished revolutions Yemen, Libya, and Tunisia after the Arab Spring - Fraihat, Ibrahim (Yale University Press, 2016)
"Post-revolution states often find that once a transition process begins, challenges can arise, such as political polarization and the threat of civil war. A respected commentator on Middle Eastern politics, Ibrahim Fraihat compares three countries grappling with political transitions in the wake of the Arab Spring: Yemen, Libya, and Tunisia. Fraihat argues that to attain enduring peace and stability, post-revolution states must engage in inclusive national reconciliation processes which include a national dialogue, a truth seeking effort, the reparation of victims' past injuries, dealing with the former regime, and institutional reform. Women, civil society, and tribes, among other social forces, can support the transition process. Fraihat's research shows how some aspects of transitions have been politicized and that each country has taken a specific approach, raising or diminishing the chances of civil war or a healthy transition. This book is based on the original field research Fraihat conducted over three years in Yemen, Libya, and Tunisia. It is the result of over 200 interviews with key figures including senior government officials, heads of political parties, revolutionary youth activists, former regime loyalists, representatives of women's and civil society organizations, military and militia commanders, tribal leaders, and members of displaced communities."--Publisher's website.